Ashes Fever : How England Won the Greatest Ever Test Series - Stafford, Ian, 1963-; Photographs by Brown, Philip (Edinburgh Mainstream Publishing, 2005)
Presenting the tensions and the twists that shaped the unforgettable Ashes series, this book explains the creation of new English sporting heroes and how cricket became the media focal point. Illustrated by 200 photographs, it relates how over three months the England cricket team created history in a manner that is unlikely to be repeated
Include Color Illustration and Appendix
Keywords: Australia -- England -- Cricket--Tournaments